p20BAP31 induces cell apoptosis via both AIF caspase-independent and the ROS/JNK mitochondrial pathway in colorectal cancer - Jiang, Xiaohan; Li, Guoxun; Zhu, Benzhi; Zang, Jingnan; Lan, Tian; Jiang, Rui; Wang, Bing (Cellular & molecular biology letters, 2023)
During cell apoptosis, the C-terminus of BAP31 is cleaved by caspase-8 and generates p20BAP31, which has been shown to induce an apoptotic pathway between the endoplasmic reticulum (ER) and mitochondria. However, the underlying mechanisms of p20BAP31 in cell apoptosis remains unclear. We compared the effects of p20BAP31 on cell apoptosis in six cell lines and selected the most sensitive cells. Functional experiments were conducted, including Cell Counting Kit 8 (CCK-8), reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) assay. Then, cell cycle and apoptosis were investigated by flow cytometry and verified by immunoblotting. Next, NOX inhibitors (ML171 and apocynin), ROS scavenger (NAC), JNK inhibitor (SP600125), and caspase inhibitor (Z-VAD-FMK) were used to further investigate the underlying mechanisms of p20BAP31 on cell apoptosis. Finally, apoptosis-inducing factor (AIF) translocation from the mitochondria to the nuclei was verified by immunoblotting and immunofluorescence assay. We found that overexpression of p20BAP31 indeed induced apoptosis and had a much greater sensitivity in HCT116 cells. Furthermore, the overexpression of p20BAP31 inhibited cell proliferation by causing S phase arrest. Further study revealed that p20BAP31 reduced MMP, with a significant increase in ROS levels, accompanied by the activation of the MAPK signaling pathway. Importantly, the mechanistic investigation indicated that p20BAP31 induces mitochondrial-dependent apoptosis by activating the ROS/JNK signaling pathway and induces caspase-independent apoptosis by promoting the nuclear translocation of AIF. p20BAP31 induced cell apoptosis via both the ROS/JNK mitochondrial pathway and AIF caspase-independent pathway. Compared with antitumor drugs that are susceptible to drug resistance, p20BAP31 has unique advantages for tumor therapy.